1999
DOI: 10.1088/0957-0233/10/11/318
|View full text |Cite
|
Sign up to set email alerts
|

Optical sensor configurations for process tomography

Abstract: This paper describes an investigation into the optimum design of optical fibre sensing arrays to be incorporated in an optical tomographic measurement system for on-line monitoring of particles and droplets. Two approaches are considered to cover opaque and transparent materials; optical path length and optical attenuation. Four flow models are investigated: single-pixel flow representing a single particle or droplet, two-pixel flow as a simple check on aliasing in the reconstructed image, half flow representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Experimental (Terzija et al, 2008;Wright et al, 2010) and numerical (Daun, 2010;Verhoeven, 1993;Ibrahim et al, 1999) CST experiments have shown that reconstruction accuracy depends strongly on the arrangement of light sources and detectors. The cost and complexity of the laser and detection optics demand that these components be used to their maximum potential.…”
Section: Beam Array Design and Optimizationmentioning
confidence: 99%
“…Experimental (Terzija et al, 2008;Wright et al, 2010) and numerical (Daun, 2010;Verhoeven, 1993;Ibrahim et al, 1999) CST experiments have shown that reconstruction accuracy depends strongly on the arrangement of light sources and detectors. The cost and complexity of the laser and detection optics demand that these components be used to their maximum potential.…”
Section: Beam Array Design and Optimizationmentioning
confidence: 99%
“…In the practical system, the various optical path projectors are required to reduce the Optical Fiber Sensors in Process Tomography aliasing. Various arrangements of the fiber sensors are considered for five types of projections [13,14] : two orthogonal projections (Figure 2a In order to ensure simple and intuitive design for Figure 2e, only a fan beam optical source was drawn. However, two other fan beam sources are needed maintain a certain emission angle with the current source on the 120 and 240 positions so that they form three fan-shaped projections together.…”
Section: Optical Structure Modelmentioning
confidence: 99%
“…In 1999, Ibrahim et al [13] used LBP and FLBP algorithms to achieve image reconstruction. Although, to keep balance among the pixels of projections can reduce errors, it still cannot meet the accuracy.…”
Section: Optical Structure Modelmentioning
confidence: 99%
“…The beam of light must diverge as little as possible to avoid overlapping of the received signals and loss of the beam intensity [3]. Three methods are used to collimate the light source.…”
Section: Optical Sensor Fixture Designmentioning
confidence: 99%